Application and trend of bioluminescence imaging in metabolic syndrome research - Li, Shirui; Wang, Kang; Wang, Zeyu; Zhang, Wenjie; Liu, Zenglin; Cheng, Yugang; Zhu, Jiankang; Zhong, Mingwei; Hu, Sanyuan; Zhang, Yun (Frontiers in Chemistry, 2023)
Bioluminescence imaging is a non-invasive technology used to visualize physiological processes in animals and is useful for studying the dynamics of metabolic syndrome. Metabolic syndrome is a broad spectrum of diseases which are rapidly increasing in prevalence, and is closely associated with obesity, type 2 diabetes, nonalcoholic fatty liver disease, and circadian rhythm disorder. To better serve metabolic syndrome research, researchers have established a variety of animal models expressing luciferase, while also committing to finding more suitable luciferase promoters and developing more efficient luciferase-luciferin systems. In this review, we systematically summarize the applications of different models for bioluminescence imaging in the study of metabolic syndrome.